Modern tomography imaging techniques in urological diseases Moderne Schnittbildgebung für urologische Erkrankungen - Schoenberg, Gita M.; Schuetz, Viktoria; Nyarangi-Dix, Joanne N.; Diehl, Steffen J.; Heiß, Rafael; Adamietz, Boris (Urologe, 2022)
Background: Radiologic imaging is important for the detection, staging and follow-up of urological tumors. Basic therapy decisions for both oncological (surgical vs. systemic therapy, e.g. in testicular cancer) and non-oncological pathologies (interventional vs. conservative therapy, e.g. for ureteral stones) depend largely on the tomographic imaging performed. Due to its almost ubiquitous availability, speed and cost-effectiveness, computed tomography (CT) plays an important role not only in the clarification of abdominal trauma and non-traumatic emergencies, but also in staging and follow-up of oncological patients. However, the level of radiation exposure, impaired renal function and allergies to iodinated contrast media limit the use of CT. Magnetic resonance imaging (MRI) can be a good alternative for many areas of application in oncological and non-oncological imaging due to its high soft tissue differentiation and functional-specific protocols but without the use of ionizing radiation. Aim: In the following, the main indications of abdominal and pelvic CT and MRI in urology and their limitations are summarized. Results: The areas of application between CT and MRI are increasingly overlapping, since the latest developments in CT continue to further reduce radiation exposure and increase contrast information, while the speed and robustness of MRI are significantly improving at the same time.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Computed tomography; Indications; Limitations; Magnetic resonance imaging; Urooncologic und non-urooncologic pathologies